Performance Analysis of Road Section and Unsignalized Intersections On Jalan Cileungsi Setu and Jalan Raya Narogong - Muhammad Isradi; Nandhita Aulia Tarastanty; Widodo Budi Dermawan; Amar Mufhidin; Joewono Prasetijo (International Journal of Engineering, Science and Information Technology, 2021)
The unsignalized intersection which is located in Cileungsi District, precisely on Jalan Cileungsi Setu and Jalan Raya Narogong, is a commercial area with dense economic activity and densely populated settlements. As a result of the dense activity, congestion occurs due to the large number of vehicles passing the road, especially during peak hours, namely the morning and evening. Seeing this problem, an analysis is needed that aims to determine the volume, performance of roads, and unmarked intersections as measured by capacity, degree of saturation, and level of service.  In analyzing this study using the Indonesian Road Capacity Manual (MKJI) 1997 method which will determine the performance of roads and intersections without signs. The data needed in this research are primary data in the form of geometric road data, traffic volume, vehicle speed data, and side friction. As well as secondary data in the form of location maps, land use, and population data. From the results of data analysis and processing, the busiest traffic flow at the intersection occurred on Sunday, November 15, 2020 at 17.30 - 18.30 WIB, the saturation degree value was 1.17 with LOS F. By doing an alternative solution, the saturation degree value was 0.68 and LOS B with placing signs are prohibited from stopping around intersections, and prohibiting the flow of traffic turning right either from the main road D to the Minor C road or from the Minor C road to the main road B. On Jalan Raya Narogong, the degree of saturation is 0.74 LOS C service, this shows that the road sections do not exceed the figure required by MKJI 1997, namely ≤ 0.75.